Cognitive Performance Among Older Adults with Subjective Cognitive Decline - Ramón López-Higes; Susana Rubio-Valdehita; David López-Sanz; Sara M. Fernandes; Pedro F. S. Rodrigues; María Luisa Delgado-Losada (Geriatrics)
Objectives: The main objective of this cross-sectional study was to investigate if there are significant differences in cognition between a group of older adults with subjective cognitive decline (SCD) and cognitively intact controls. Methods: An initial sample of 132 older people underwent an extensive neuropsychological evaluation (memory, executive functions, and language) and were classified according to diagnostic criteria. Two groups of 33 subjects each, controls and SCD, were formed using an a priori case-matching procedures in different variables: age, biological sex, years of education, cognitive reserve, and Mini-Mental State Exam. Results: The mean age and standard deviation in the control group were equal to 70.39 ± 4.31 years, while in the SCD group, they were 70.30 ± 4.33 years. The number of males (n = 9) and females (n = 24) was equal in both groups; the means of years of education were also quite similar. SCD participants have a significantly lower mood than the controls. Significant differences between groups were obtained in delayed recall, inhibitory control, and comprehension of sentences not fitted to canonical word order in Spanish. A logistic regression revealed that a lower score on the Stroop’s interference condition is associated with a higher likelihood of having SCD. Finally, ROC analysis provided a model that performs better than random chance, and a cut-off score in Stroop’s interference condition equal to 49 was suggested for clinically differentiating the two groups. Conclusions: This study highlights that, compared to a matched control group, participants with SCD showed subtle but significant neuropsychological differences.